Ti-6a1-4V Alloy Coated With Bioceramics By Using Radiofrequency Plasma Sputtering Technique - Ali, Raheem Lafta (2016)
Biomaterials are synthetic materials used to replace part of a living organ or to function in intimate contact with living tissue. Titanium and Ti-6Al-4V alloy are among the most commonly used implant materials, because of the good corrosion resistance, excellent strength and ductility. Elements of Ti-6Al-4V alloy cause allergic response and degeneration of muscle tissue. The subsequent release of these elements into the body system is fatal for the long term application of this alloy in the human body. Therefore, the aim of this study was to improve the structure properties and the biocompatibility of bioceramic coated Ti-6Al-4V by using radio frequency plasma technique RF. Annealing of the as-sputtered films was necessary to change the amorphous coating to a crystalline coating.